ACTR-13. A BAYESIAN ADAPTIVE RANDOMIZED PHASE II TRIAL OF BEVACIZUMAB VERSUS BEVACIZUMAB PLUS VORINOSTAT IN ADULTS WITH RECURRENT GLIOBLASTOMA FINAL RESULTS. (5th November 2018) - Puduvalli, Vinay; Wu, Jing; Yuan, Ying; Armstrong, Terri; Wu, Jimin; Giglio, Pierre; Xu, Jihong; Colman, Howard; Walbert, Tobias; Raizer, Jeffrey; Groves, Morris; Iwamoto, Fabio; et al.
Abstract: BACKGROUND: Bevacizumab improves outcome and reduces symptoms in patients with recurrent glioblastoma (GBM). However, GBMs develop adaptive resistance to bevacizumab- mediated angiogenesis inhibition resulting in tumor recurrence. We hypothesized that vorinostat, a histone deacetylase (HDAC) inhibitor, with pleotropic antiangiogenic effects, would delay emergence of resistance to bevacizumab therapy and improve clinical outcome. METHODS: In this multicenter phase II trial utilizing a novel Bayesian design, patients with recurrent glioblastoma were adaptively randomized to bevacizumab alone or bevacizumab+vorinostat based on a primary endpoint of progression-free survival (PFS) such that patients had a higher likelihood of receiving the more efficacious treatment. Secondary end points were overall survival (OS) and quality of life assessment (MDASI-BT). Eligible patients were adults (≥ 18 yrs) with histologically confirmed GBMs recurrent after prior radiation and temozolomide therapy, adequate organ function, KPS≥ 60, and no prior bevacizumab/HDAC inhibitors. RESULTS: Ninety patients (bevacizumab+vorinostat:49, bevacizumab:41) were enrolled and 74 were evaluable for PFS (bevacizumab+vorinostat:44, bevacizumab:30). Grade 3 or greater toxicities in 85 evaluable patients included hypertension (n=37), neurological changes (n=2), anorexia (n=2), infections (n=9), wound dehiscence (n=2), DVT/PE (n=2), and colonic perforation (n=1). There was one treatment-related death due to pulmonary embolism. Upon multivariate analysis for bevacizumab+vorinostat vs bevacizumab, median PFS (3.7 vs. 3.9 months, p =0.94, HR 0.63 [95% CI 0.38, 1.06, p =0.08]) or median OS (7.8 vs. 9.3 months, p =0.64, HR 0.93 [95% CI 0.5, 1.6, p =0.79]) were not significantly different between the two arms. Ongoing analyses of patient reported outcomes (MDASI-BT) and plasma biomarkers will be reported. CONCLUSIONS: Combining bevacizumab with vorinostat did not result in improved PFS or OS compared with bevacizumab alone in patients with recurrent GBM. This trial is the first to test a Bayesian PFS-based adaptive randomized design in patients with primary brain tumors and demonstrates the feasibility of using adaptive randomization in a multicenter setting.